SUBSTANTIATION OF CHANGES IN THE CERTIFICATION OF THE TRACTOR DRIVER’S WORKPLACE IN MODERN MACHINE-TRACTOR UNITS - Krainiuk, M.; Krainiuk, O.; Buts, Yu.; Barbashyn, V. (Municipal economy of cities. Series: «Economy science», 2024)
The study aims to identify possible changes in the working conditions of tractor drivers under the computerisation of workplaces and to develop proposals for changing the requirements for sanitary standards in the design of tractors and agricultural machinery. The article analyses the impact of modern technologies on the working conditions of tractor drivers in agriculture. It investigates various aspects of work, including using on-board computers, air conditioning, and satellite navigation, and their impact on workers’ health. The authors consider health risks, such as increased noise levels and work with on-board computers, and reveal the lack of consideration of these aspects in regulatory documents. In particular, we have found that using on-board computers significantly simplifies the process of controlling agricultural machinery but can lead to increased noise and vibration levels, negatively affecting workers’ health. Some studies have shown that prolonged work with on-board computers can lead to the development of occupational diseases, such as musculoskeletal disorders, impaired vision, and others. In addition, air conditioning in tractor cabs can cause colds due to sudden temperature changes and increase the risk of legionella infection due to the water condensation accumulation in ventilation systems. The research also found that the legal and regulatory documents governing the working conditions of tractor drivers do not consider the use of modern technologies, which creates gaps in worker protection. Regulatory documents should contain requirements for the parameters of monitors and their placement in the working area of tractor drivers in agricultural production, such as adjusting the reflectivity of the screen, the main adjusted visual characteristics of monitors, and the location of video terminals in the tractor cab without being directly in the line of sight. It is necessary to develop measures to prevent the overwork of tractor drivers. Regulations should include rules for the use of air conditioners, as well as for cleaning air conditioning ducts and replacing filters on time. The general conclusion is that there is a need to strengthen the regulation of tractor drivers’ working conditions and to include requirements for using modern technologies in the relevant regulations. These measures will ensure the safety and health of workers in agriculture and reduce the risk of occupational diseases.